'Dorsal vessels'? 3D-reconstruction and ultrastructure of the renopericardial system of Elysia viridis (Montagu, 1804) (Gastropoda: Sacoglossa), with a discussion of function and homology. (12th November 2018) - Neusser, Timea P; Hanke, Felix; Haszprunar, Gerhard; Jörger, Katharina M
Abstract: So-called 'dorsal vessels' are poorly described network-like structures associated with the renopericardial system and located dorsally beneath the epidermis in different groups of heterobranch gastropods. So far, homology assumptions among the different 'dorsal vessel systems' have been hampered by a lack of comparative histological and ultrastructural data. In the present study, we provide the first detailed 3D-reconstruction of a sacoglossan 'dorsal vessel system', based on histological semithin sections combined with ultrastructural data. The renopericardial system of Elysia viridis comprises a monotocardial heart, surrounded by a sac-like pericardium that is connected with a ventrally situated kidney. Our histological data show that the 'dorsal vessels' connect to the atrium, rather than the pericardium as previously reported. The 'dorsal vessels' investigated herein entirely lack an endothelium and are thus more correctly termed 'dorsal haemolymph sinuses'. With some exceptions, there is a conspicuous correlation between the ability of Sacoglossa to retain plastids from their algal prey and the presence of dorsal haemolymph sinuses. Thus, the latter might enhance circulation and form an internal recycling system that transports oxygen from the site of photosynthesis to the organs and carbon dioxide in the opposite direction. There are considerable structural and histological differences in the 'dorsal vessels' of Sacoglossa, Acochlidimorpha and likely Nudibranchia, probably reflecting independent developments to cope with different environmental stress factors and thus to adapt to various ecological niches. Further comparative microanatomical and ultrastructural (re)investigation of missing lineages are required for a better understanding of the variability of the renopericardial complex in heterobranch gastropods and of modifications of the circulatory system.